Hermeneutics of Peace: Local Religious Elites and the Promotion of Interfaith Harmony in Central Java - Moh Muhtador; Irzum Farihah; Fathul Mufid (Millati: Journal of Islamic Studies and Humanities, 2025)
Local religious elites play a strategic role in constructing interfaith peace in their respective regions, but their existence has not yet received serious attention from scholars for study and introduction. This article aims to reveal two important things: the involvement of local religious elites and the meaning of peace as they believe it to be. This paper uses a qualitative method with field studies covering Pati, Kudus, and Blora as the locus of study, using hermeneutics to analyze the role and meaning of peace within local religious elites. The findings of this article indicate that interfaith harmony is primarily constructed within formal religious spaces and informal social settings through various arenas. The Quran and hadith are foundational texts believed to contain messages of eternal peace. This study contributes to understanding patterns in contemporary Islamic studies related to interfaith issues.